Erratum: Model of Success: Extension Services Helping Ugandan Youth Find A Career in Agriculture - JIAEE Editors (Journal of International Agricultural and Extension Education, 2024)
Correction: The DOI of the article "Lamm, K. W., Mulvaney, C., Lamm, A. J., Davis, K., Masambuka-Kanchewa, F., & Nahdy, S. (2021). Model of Success: Extension Services Helping Ugandan Youth Find A Career in Agriculture. Journal of International Agricultural and Extension Education, 28(3), 7-13” was incorrect as published. The correct DOI is: 10.5191/jiaee.2021.28301